Gerenciamento de resíduos de construção civil de acordo com a resolução CONAMA 307/02: estudo de caso para um conjunto de obras de pequeno porte - Alex Fabiane Fares da Silva (2007)
In Brazil and abroad, the construction sector is well know as the largest user of natural resources and the largest producer of waste. The waste disposal becomes more difficult each day due to the high costs of transportation and also to the difficulty in finding areas which can achieve environmental requirements. In this context, the Brazilian National Environmental Committee (Conselho Nacional do Meio Ambiente, CONAMA), published in 2002 the CONAMA Resolution 307, establishing guidelines, criteria and procedures for the management of the waste generated by civil construction, assigning to the municipalities and to the large producers the responsibility to separate and dispose their waste in accordance with a suggested classification. According to research data, the largest proportion of civil construction wastes produced daily in Brazil comes from informal sites, involving small constructions, refurbishment and demolition activities. This way the small producers become responsible for the largest proportion of the waste generated. In this context, this research describes the results of the implementation of the mentioned resolution guidelines in a group of small construction sites in the area of Belo Horizonte, Minas Gerais (Brazil). Three new construction sites (residential, commercial and industrial) and a refurbishment site were chosen. They were monitored and, beyond the measurement of the input materials and the waste produced, indexes, which can be used in similar construction sites, were developed. The costs of each management phase were also obtained. The research conducted showed a large difference in the amount of waste produced in refurbishment (684 kg/m2) and new construction sites (average of 97,75 kg/m2). Its segregation at the production point allowed an improvement in organisation, hygiene conditions and occupational safety, as well as a simpler recycling and appropriate final disposal. It can also be ighlighted the potential reuse of the waste in the construction sites, the low cost of its management (average of 0,22% to new construction activities) and the fact that such management activities did not change the physical timeline of the construction sites assessed